Short report: Molecular evidence of Trichostrongylus colubriformis and Trichostrongylus axei infections in humans from Thailand and Lao PDR - Issarapong Phosuk (2018)
Human trichostrongylosis has been reported in Thailand. Recent reports in Lao People's Democratic Republic concerning species identification urged us to investigate species distribution in Thailand. We report eight human cases in Thailand and Lao People's Democratic Republic that were found to be infected by Trichostrongylus colubriformis and T. axei identified and confirmed by molecular techniques. This evidence is the first molecular evidence of human T. colubriformis and T. axei infection in Thailand. Infection by these two species was apparently epidemic in these areas. It is necessary to proceed with more comprehensive veterinary and epidemiologic studies to enable the practical prevention and control of this parasitic zoonosis. Copyright © 2013 by The American Society of Tropical Medicine and Hygiene.